Triglyceride-glucose index is associated with heart failure with preserved ejection fraction in different metabolic states in patients with coronary heart disease - Li, Zhu; Fan, Xiang; Liu, Yijia; Yu, Lu; He, Yuanyuan; Li, Lin; Gao, Shan; Chen, Wei; Yang, Rongrong; Yu, Chunquan (Frontiers in Endocrinology, 2024)
Background The triglyceride-glucose (TyG) index is a surrogate indicator of insulin resistance. Therefore, we aimed to determine the association between TyG index and heart failure (HF) with preserved ejection fraction (HFpEF) in patients with coronary heart disease (CHD) and to explore whether such associations would be modified by different metabolic states. Methods Among 107,301 CHD patients, 62,794 were included to analyze the relationship between the TyG index and HF. Among them, 8,606 patients who had undergone echocardiography were included to identify different types of HF, including HF with reduced ejection fraction (HFrEF), HF with intermediate-range ejection fraction (HFmrEF), and HFpEF. Among them, 1896 patients were diagnosed with HFpEF. Logistic regression was used to analyze the relationship between the TyG index and HFpEF in CHD patients. In addition, the association between TyG index and HFpEF according to sex, age, blood lipids, and blood pressure was assessed. Results A baseline analysis of CHD patients divided into four groups according to the tertile level of the TyG index showed significant differences in the related parameters between the groups. In the multi-adjusted models, the TyG index was significantly associated with the risk of HFpEF (odds ratio [OR]: 1.17; 95% confidence interval [CI]: 1.09–1.25). After adjustment for multivariates, TyG index levels for T2 (OR: 1.33; 95% CI: 1.16–1.52) and T3 (OR: 1.52; 95% CI: 1.32–1.74) were associated with increased OR in HFpEF. In addition, the TyG index of CHD patients was significantly associated with HFpEF in older adults aged > 60 years (OR: 1.20; 95% CI: 1.11–1.29), hypertension (OR: 1.27; 95% CI: 1.17–1.37), and dyslipidemia (OR: 1.15; 95% CI: 1.08–1.24). Moreover, the OR (OR: 1.23; 95% CI: 1.11–1.36) in women is higher than in men (OR: 1.17; 95% CI: 1.02–1.22, indicating a stronger association between TyG index and HFpEF in women. Conclusions Our findings demonstrated a significant association between TyG index and HFpEF in CHD patients. Furthermore, TyG index was independently associated with HFpEF in hypertension, dyslipidemia, and older patients (aged > 60 years). In addition, the association between the TyG index and HFpEF in CHD patients differed according to sex.